The logic of patent claims - Zaleski, Jacek (Kwartalnik Nauk o Przedsiębiorstwie, 2014)
This article presents selected legal aspects related to the protection of intellectual property during the procedure of the patent claims. Artykuł przedstawia wybrane aspekty prawne związane z ochroną własności intelektualnej podczas procedury roszczenia patentowego.